К расчету промывки долот режуще-истирающего типа - Казьмин, А.О.; Супрун, М.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
The paper subscribes the correlation between a temperature of the cutter and a drilling fluid velocity. The correlation contains some heat-and-physical features of the fluid and constructive variables of a cutters. This allows to use it in more precision calculations with wash systems of new drills.